Ant Based Cross Layered Optimization Protocol for Wireless Multimedia Sensor Network with Fuzzy Clustering - Dipali Parag Adhyapak; Sridharan Bhavani; Aparna Pradeep Laturkar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Wireless Multimedia Sensor Network (WMSN) is embedded with large number of Audio, Video and scalar sensor nodes which can able to retrieve the multimedia information from the environment. WMSN has several challenges such as life time of the network, Memory requirement, Coverage, Bandwidth and QoS metrics. Hence selection of routing algorithm is crucial in WMSN. Again interdependencies of the protocol layer cannot be neglected to improve the network performance. Clustering in WMSN is challenging task in order to increase network lifetime and to improve the communication. Hence Fuzzy clustered Ant based cross layer protocol (FCAXL) is proposed. In this paper performance analysis of ant based cross layer optimization protocol with fuzzy clustering based on number of nodes and packet size is done. Simulation results shows that Fuzzy clustered ant based cross layer optimization protocol performs best as compared to AntSenseNet routing protocol, Cross layer routing protocol and Ant based cross layer routing protocol in terms of QoS parameters such as Throughput, Packet delivery ratio and delay. Hence the life time of the network increases.